The risk factors of hamstring strain injury induced by high-speed running - Tokutake, G.; Kuramochi, R.; Murata, Y.; Enoki, S.; Koto, Y.; Shimizu, T. (Journal of Sports Science & Medicine, 2018)
Hamstring strain injury is a multifactorial and complex problem involving interactions among various factors. Information about risk factors for this injury is inconsistent among studies because the strong effects of confounding factors and injury situations are often ignored. We investigated the relationship between hamstring strain induced by high-speed running and intrinsic risk factors, including hip muscle morphology and function, by excluding the influences of confounding factors. Sixty-one male track and field athletes (age, 19.6 ± 1.1 years; 95% confidence interval, 19.3-19.9) who often performed high-speed running were monitored throughout one season. Before the season, we measured hip and knee strength, muscle thickness of the gluteus maximus and biceps femoris, and hip and knee joint range of motion (ROM). We also obtained information about each athlete`s history of hamstring injury by questionnaire. Eighteen athletes sustained hamstring strain injuries induced by high-speed running. Eighteen uninjured athletes who had the same profile of confounding factors as the injured athletes were selected as controls. Previously injured athletes had a significantly higher injury rate than uninjured athletes (p < .05; odds ratio, 2.85). No other measurements had a significant relationship with the occurrence of injury. However, passive hip ROM (flexion and extension) tended to be larger in the injured than control group. A history of hamstring strain was a strong risk factor for hamstring strain injury, and it may affect other factors. Therefore, the risk factors for hamstring strain injury should be investigated by eliminating the impact of a history of hamstring strain.